Land Vulnerability Analysis for Determining Land Rehabilitation Directions for Soil Conservation in Conservation District: Case Study of Tamansari District, Boyolali Regency - Alvian Febry Anggana; Endang Savitri; S. Andy Cahyono; Rahardyan Nugroho Adi; Pamungkas Buana Putra; Mahardhika N. R. P; Rama Zakaria; Muslim Afandi (Postgraduate, University of Mataram, 2024)
Land vulnerability is a condition where a land is sensitive to environmental changes or human pressure. This certainly affects the productivity, quality, and sustainability of the land to recover from the impacts that may occur due to land changes. This problem certainly has a direct or indirect effect on the socio-economic life of the community. The purpose of this study is to map and recommend directions for Land Rehabilitation and Soil Conservation (RLKT) in Tamansari District, which in its development is in the Klaten Regency area, Subdas Pusur DS. The analysis method uses overlay of erosion land vulnerability, flood vulnerability, land cover, and land use capability. The results of the study indicate that the area of vulnerable land that needs to be RLKT is 4,375.7 ha covering 10 villages. The largest village that needs to be RLKT is Jemowo Village (668.9 ha) and Mriyan Village (644.7 ha). Land Rehabilitation and Soil Conservation Directions in the form of Reforestation with vegetation, cover crops, compost, reservoirs, rorak, terrace reinforcement, ridges, SPA, infiltration wells. The RLKT Direction is expected to be able to control land vulnerability to erosion, land vulnerability to flooding and water management so that it is expected to be able to improve the welfare of the community in the Tamansari District area.